Media Criticism: Class Fantasy and Ideology in the Movie Ganj-e Qaroon - Rabani, Rasoul; Adibi, Mehdi; Aqababaee, Ehsan (Richtmann Publishing, 2012)
Subjects due to their class position may construct specific fantasies. Class fantasy, one of the given fantasies, isconstructed by lower-classes in the society. This study is to critically scrutinize this type of fantasy in media discourse data.Furthermore, as ideology is a means by which cinema apparatus sutures audience within movie narration, the movie ideologyand its relation with the given fantasy will be discussed as well. Indeed, the paper presents an attempt to illustrate how movies,through the construction of the fantasy, serve to justify the prevailing ideologies at the time. A case in point is melodrama. Thedata are extracted from one the most popular movies in the history of Iranian cinema, Ganj-e Qaroon (meaning Qaroon’sTreasure). Analysis of the data is done within the frameworks of Bordwell (1995); Cormack (1992); and Zizek (2008a). Findingsshow that the class fantasy is constructed through the movie. That is the hero, reaching the object-cause of desire namely thegirl of narration, may fill the class gap; however, a change in his position causes the object to lose its significance. Concerningthe movie ideology, results indicate that the movie ideology, i.e. the class ideology, proposes class coexistence in peace.Indeed, the movie not only represents class fantasy but also uses the end of fantasy in its favor.